Physicochemical compatibility studies of triclosan and flurbiprofen with excipients of pharmaceutical formulation using binary, ternary, and multi-combination approach - Nafiu Aminu; Siok-Yee Chan; Momoh A. Mumuni; Nura Muhammad Umar; Nuhu Tanko; Sirajo Abubakar Zauro; Abdulmalik Aminu; Seok-Ming Toh (SpringerOpen, 2021)
Abstract Background The aim of the study was to evaluate the suitability of triclosan (TCS) and flurbiprofen (FLB) with poly-ε-caprolactone (PCL), chitosan (CS), and Kolliphor® P188 (KP) for possible application in the design of nano-formulations. Results Differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), and scanning electron microscopy (SEM) revealed the physical characteristics of the various sample compositions without any apparent interaction. The Fourier transform infrared spectroscopy (FTIR)'s spectra of the physical mixtures showed their characteristic absorption bands with broadening and overlapping of bands in some instances, but no appearance of new bands was observed. Conclusion The study revealed the physical form stability of the evaluated components after the storage period and lack of definite pharmaceutical incompatibility between them. Thus, the selected drugs and excipients could be used for the development of pharmaceutical nano-formulations.